2013
DOI: 10.1089/vim.2012.0055
|View full text |Cite
|
Sign up to set email alerts
|

Biological Properties of H5 Hemagglutinin Expressed by Vaccinia Virus Vector and its Immunological Reactivity with Human Sera

Abstract: A recombinant vaccinia virus harboring the full length hemagglutinin (HA) gene derived from a highly pathogenic avian influenza A/Thailand/1(KAN-1)/2004 (H5N1) virus (rVac-H5 HA virus) was constructed. The immunogenicity of the expressed HA protein was characterized using goat antiserum, mouse monoclonal antibody, and human sera. The expressed HA protein localized both in the cytoplasm and on the cytoplasmic membrane of the thymidine kinase negative cells infected with the rVac-H5 HA virus, as determined by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…HA and NA genes, which encode major viral surface glycoproteins, are hypervariable and continuously evolve ( Gutiérrez et al, 2009 ). The biological properties and immune responses against HA and NA glycoproteins of these H5N1 viruses have been previously characterized ( Panaampon et al, 2012 ; Noisumdaeng et al, 2013 ; Noisumdaeng et al, 2014 ; Changsom et al, 2016 ; Noisumdaeng et al, 2021 ). This study comprehensively analyzed the genetic evolution of Thai H5N1 HA and NA nucleotide sequences available in the GenBank database from 2003 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…HA and NA genes, which encode major viral surface glycoproteins, are hypervariable and continuously evolve ( Gutiérrez et al, 2009 ). The biological properties and immune responses against HA and NA glycoproteins of these H5N1 viruses have been previously characterized ( Panaampon et al, 2012 ; Noisumdaeng et al, 2013 ; Noisumdaeng et al, 2014 ; Changsom et al, 2016 ; Noisumdaeng et al, 2021 ). This study comprehensively analyzed the genetic evolution of Thai H5N1 HA and NA nucleotide sequences available in the GenBank database from 2003 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Sera, plasma and peripheral blood mononuclear cells (PBMCs) were obtained from 37 participants including four H5N1 Thai survivors, 10 H3N2 patients and 23 healthy individuals (Kitphati et al, 2009;Noisumdaeng et al, 2013;Noisumdaeng et al, 2014). Survivor nos.…”
Section: Human Subjects and Blood Specimenmentioning
confidence: 99%
“…Recombinant vaccinia virus carrying H5N1 NP gene inserted in the pSC11 plasmid backbone (rVac-NP virus) or the recombinant virus carrying only the pSC11 backbone (rVac-pSC11 virus) were constructed in our laboratory. The viruses were propagated and titrated in Thymidine kinase negative (TK − ) cells maintained in Dulbecco's modified eagle medium (DMEM) (Gibco) supplemented with 10% FBS plus penicillin and streptomycin (Noisumdaeng et al, 2013;Noisumdaeng et al, 2014). The virus stocks were kept at −80 • C until used.…”
Section: Recombinant Vaccinia Virusesmentioning
confidence: 99%
“…Many laboratories have initiated research on the use of naturally evolved strains for vaccination, especially research on improving the safety of VV and other poxviruses. In particular, many studies have shown that VV is useful for the study of vaccine vectors and exogenous gene expression systems (Garcia-Arriaza et al, 2013 ; Noisumdaeng et al, 2013 ; Adelfinger et al, 2014 ; Remy-Ziller et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%